Case Report: Gene expression profiling of COVID-19 vaccination-related lymphadenopathies reveals evidence of a dominantly extrafollicular immune response - Menter, Thomas; Zinner, Carl P.; Berger, Christoph T.; Went, Philip; Tzankov, Alexandar (Frontiers in Immunology, 2023)
mRNA-based vaccines against SARS-CoV-2 have been proven to be very efficient in preventing severe COVID-19. Temporary lymphadenopathy (LA) has been observed as a common adverse event following immunization. Here we describe a case series of three female patients with prominent local to generalized LA after SARS-CoV-2 mRNA-1273 vaccination, which led to lymph node biopsy due to the suspicion of lymphoma or metastasis. All three patients morphologically showed similar patterns of follicular hyperplasia and especially extrafollicular blast activation. Two of the three patients only had short-lasting humoral immune responses to the vaccination. Gene expression profiling (GEP) using the HTG Immune response panel revealed that all three patients clustered together and clearly differed from the GEP-patterns of COVID-19, infectious mononucleosis and non-specific follicular hyperplasia. The closest similarities were seen with lymph nodes showing extrafollicular activation of B-blasts as well as hemophagocytosis. The GEP of the vaccinationinduced LA was reminiscent of an immune response with little potential of immunologic memory. mRNA-1273 vaccination-induced LA may to a certain extend reflect disordered immune response with potentially poor immunologic memory in affected individuals.